Sufism in Contemporary Scholarship: Mapping the Evolution and Knowledge Production of Sufi Studies through Bibliometric Analysis - Firdaus Wajdi (Master's Program in Sociology, Faculty of Social and Political Sciences, Universitas Negeri Surabaya, 2026)
This study maps the evolution and geopolitics of knowledge production in contemporary Sufi studies through a bibliometric analysis of 2,180 Scopus-indexed documents published between 1894 and 2025 across 613 publication sources. Using the Bibliometrix package in R, the analysis examines publication growth, authorship, country distribution, collaboration patterns, and thematic development. The findings indicate an annual publication growth rate of 3.59%, demonstrating sustained scholarly interest in Sufism. Religion and the human remain central themes, while more recent publications increasingly engage with Islamism, politics, modernity, and Muslim identity. Nevertheless, the global visibility of Sufi scholarship remains uneven. Publication and authorship networks are concentrated in Anglophone academic centres, particularly the United Kingdom and the United States, while Pakistan emerges as an important Southern node. This pattern reveals a disparity between the regions in which Sufi traditions are historically embedded and the academic institutions that acquire authority to classify, interpret, and circulate knowledge about them. The dataset also contains engineering publications using SUFI as an acronym, underscoring the need for more rigorous bibliographic curation. From a Southern sociological perspective, this study argues that Sufism should not be treated merely as an empirical object located in the Global South. Southern archives, languages, concepts, institutions, and scholarly communities must also be recognised as sources of sociological theory and epistemic authority. The study contributes to debates on the geopolitics of knowledge in Islamic studies and proposes a more reflexive and regionally grounded agenda for future Sufi scholarship.